Responsibilities of the repair student in museums - Matyazov Atabek; Abdudaeva Sadokat (International Journal on Orange Technologies, 2020)
This article provides information to museum repairmen on all methods of working in the museum, including the work carried out in the museum stock, repair and conservation.